A self-calibrated tissue viability sensor for free flap monitoring - Berthelot,ME; Yang,GZ; Lo,B (IEEE Journal of Biomedical and Health Informatics, 2017)
In fasciocutaneous free flap surgery, close postoperative monitoring is crucial for detecting flap failure, as around 10% of cases require additional surgery due to compromised anastomosis. Different biochemical and biophysical techniques have been developed for continuous flap monitoring, however, they all have shortcoming in terms of reliability, elevated cost, potential risks to the patient and inability to adapt to the patient's phenotype. A wearable wireless device based on near infrared spectroscopy (NIRS) has been developed for continuous blood flow and perfusion monitoring by quantifying tissue oxygen saturation (StO2). This miniaturized and low cost device is designed for postoperative monitoring of flap viability. With self-calibration, the device can adapt itself to the characteristics of the patients' skin such as tone and thickness. An extensive study was conducted with 32 volunteers. The experimental results show that the device can obtain reliable StO2 measurements across different phenotypes (age, sex, skin tone and thickness). To assess its ability to detect flap failure, the sensor was validated with an animal study. Free groin flaps were performed on 16 Sprague Dawley rats. Results demonstrate the accuracy of the sensor in assessing flap viability and identifying the origin of failure (venous or arterial thrombosis).